Peramalan Penjualan Pupuk Urea Dengan Menggunakan Metode Single Exponential Smoothing - Fadli Muhammad; Sukanta Sukanta; Aria Dewanta (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2022)
The implementation of a sales forecasting strategy is very important to be done in the company. But there are still many companies that still have not implemented this strategy, such as pt. Pupuk Kujang Cikampek. This company is a state-owned enterprise that handles the manufacture of domestic fertilizers In addition to making subsidized urea fertilizer, this company also makes non-subsidized fertilizers. Unlike subsidized fertilizers whose production has been determined by the government, this non-subsidized fertilizer often undergoes changes in the amount of production and there is often a buildup of finished goods supplies. This research was made to find out the amount of estimated value of the next period of sales in jumbo-sized non-subsidized urea fertilizer products with the method Single Exponential Smoothing and Mean Absolute Percent Error (MAPE). Based on the research that has been done, the forecasting results for the next production period have experienced stability and the percentage value of forecasting is 20.66% which means that the forecasting model carried out is feasible. Previously, according to the data obtained, sales in 2019 were patterned as unstable. Where every month experiences sales that rise and fall drastically. Penerapan strategi peramalan penjualan penting sekali dilakukan pada perusahaan. Namun masih banyak perusahaan yang masih belum menerapkan strategi ini, seperti pada PT. Pupuk Kujang Cikampek. Perusahaan ini merupakan badan usaha milik negara yang menangani pembuatan pupuk dalam negeri Selain membuat pupuk urea bersubsidi, perusahaan ini juga membuat pupuk non subsidi. Berbeda dengan pupuk bersubsidi yang produksinya telah ditentukan oleh pemerintah, pupuk non subsidi ini sering kali mengalami perubahan dalam jumlah produksi dan sering terjadi penumpukan persediaan barang jadi. Penelitian ini dibuat untuh mengetahui jumlah nilai peramalan penjualan periode selanjutnya pada produk pupuk urea non subsidi ukuran jumbo dengan metode Single Exponential Smoothing dan Mean Absolute Percent Error (MAPE). Berdasarkan penelitian yang sudah dilakukan, didapatkan hasil peramalan untuk periode produksi selanjutnya mengalami kestabilan dan nilai persentase peramalan 20,66 % yang artinya model peramalan yang dilakukan layak. Sebelumnya menurut data yang didapatkan, penjualan tahun 2019 berpola tidak stabil. Dimana setiap bulannya mengalami penjualan yang naik turun secara drastis.